PARTISIPASI MASYARAKAT DALAM PENERAPAN COMMUNITY BASED TOURISM (CBT) DI KAMPUNG WISATA DAYUN KABUPATEN SIAK PROVINSI RIAU - Putri, Andriani Mahenda Putri; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Kampung Dayun, Siak Regency, Riau Province is one of the tourist villages that uses the principle of Community Based Tourism (CBT) in its development process. Community Based Tourism (CBT) is a concept of developing tourist destinations by empowering local communities to be directly involved in tourism activities. The purpose of this study is to determine the form of community participation in the application of Community Based Tourism (CBT) in Kampung Wisata Dayun, Siak Regency, Riau Province and to determine the impact that occurs in the process of implementing Community Based Tourism (CBT) in Kampung Wisata Dayun, Siak Regency, Riau Province. This research employs a qualitative descriptive research method. The theory used in this study uses four stages according to Cohen and Opchoff in Mulyadi, namely decision making, implementation, benefit taking and evaluation. The results of this study are the Forms of Community Participation in the Implementation of Community Based Tourism (CBT) in Dayun Tourism Village, Siak Regency, Riau Province which has an impact on community involvement in various activities without coercion. increase the amount of income, improve the quality of human resources, create local tour guides, open job vacancies, and increase the income of local communities in real terms. Keywords: Community Based Tourism, Dayun Tourism Village, Impact